The efficacy and safety of non operative management in abdominal injury in a high volume but resource stretched setting - Radjou, Angeline Neetha; Paramsivam, Jayakumar; S., Mohan Kumar (International Surgery Journal, 2016)
Background:Injury to the abdomen is a significant cause of mortality and morbidity. The study was to describe the clinical profile and analyse the efficacy and safety of Non Operative Management (NOM) in a high volume but resource stretched setting. Methods: A prospective observational study was conducted on patients with abdominal injury. The clinical profile; interventions, morbidity and mortality were studied. Results:Of the 130 cases of serious injury to the abdomen, 16 patients died during resuscitation,52 were taken up for immediate laprotomy due to hemodynamic instability/peritonitis and 62 patients were initially managed by NOM. The failure rate in NOM was 34% mainly due to delayed manifestations of bowel injury. However the mortality rate directly attributable to missed bowel injury was 2 %. Conclusions:Injury to the abdomen is one of the leading causes of morbidity and mortality. The efficacy and safety of NOM in our facility is comparable to published validated studies. The mortality rate directly attributable to missed bowel injury was 2 %, is acceptable to avoid the 50% chance of negative/non therapeutic laprotomy. We have identified a few red herrings in our study ,which could further increase safety, in our high volume but resource stretched setting.